2005
DOI: 10.1007/s00468-005-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Salinity effect on plant growth and leaf demography of the mangrove, Avicennia germinans L.

Abstract: We assessed the effect of salinity on plant growth and leaf expansion rates, as well as the leaf life span and the dynamics of leaf production and mortality in seedlings of Avicennia germinans L. grown at 0, 170, 430, 680, and 940 mol m −3 NaCl. The relative growth rates (RGR) after 27 weeks reached a maximum (10.4 mg g −1 d −1 ) in 170 mol m −3 NaCl and decreased by 47 and 44% in plants grown at 680 and 940 mol m −3 NaCl. The relative leaf expansion rate (RLER) was maximal at 170 mol m −3 NaCl (120 cm m −2 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 28 publications
1
36
0
3
Order By: Relevance
“…We estimated that the time required for a leaf to reach the measured concentration in each salinity treatment decreased from 72 to 29 days as salinity increased from 0 to 940 mol NaCl m -3 . This time is reasonable considering that the half-life of a leaf in A. germinans decreases from 425 to 96 days under the same salinity treatments (Suárez and Medina, 2005). Therefore, transpiring leaves of A. germinans do accumulate large amounts of ions during their expansion and secretion rates are enough to maintain adequate physiological levels of salt in the mature leaf (Atkinson et al, 1967;Ball, 1988).…”
Section: Leaf Ion Concentrationmentioning
confidence: 91%
“…We estimated that the time required for a leaf to reach the measured concentration in each salinity treatment decreased from 72 to 29 days as salinity increased from 0 to 940 mol NaCl m -3 . This time is reasonable considering that the half-life of a leaf in A. germinans decreases from 425 to 96 days under the same salinity treatments (Suárez and Medina, 2005). Therefore, transpiring leaves of A. germinans do accumulate large amounts of ions during their expansion and secretion rates are enough to maintain adequate physiological levels of salt in the mature leaf (Atkinson et al, 1967;Ball, 1988).…”
Section: Leaf Ion Concentrationmentioning
confidence: 91%
“…R. stylosa saplings grown at salinities greater than 25 % seawater, have sharp and significant decreases in leaf, stem and root dry weights (Clough, 1984). In Avicennia germinans high salinities increase leaf mortality and reduce leaf expansion significantly (Suárez & Medina, 2005). A comparative study in A. germinans, L. racemosa and R. mangle showed that elevated environmental salinities lead to increased osmolality of the leaf sap and leaf area reduction, which was especially pronounced in R. mangle (Medina & Francisco, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Once the capacity of cells to store salts is exhausted, salts build up in the intercellular space leading to cell dehydration and death (Sheldon et al 2004). At higher salinity, the expansion rate of the leaf area reduces together with a decrease in leaf production rate and in leaf size leading to the death of the plant (Suarez and Medina 2005).…”
Section: Introductionmentioning
confidence: 99%